the Fish as food in viceregal Peru - Coloma Porcari, César (2020)
This research work offers documented information on the human consumption of fish in viceregal Peru, collecting what is recorded by Ricardo Palma in his Traditions, as well as by Juan de Arona (Pedro Paz Soldán y Unánue), Dr. Ernst W. Middendorff and Fray Bernabé Cobo (1653). The list of fish is ordered alphabetically, and it is indicated whether they were consumed fresh, dried or salted, as indicated by these authors.